Pengaruh Kualitas Produk dan Kualitas Pelayanan terhadap Kepuasan Pelanggan di PT X - Ahmad Fakhrurozi Naer; Zahra Zahra (STIKes Ibnu Sina Ajibarang, 2024)
Business activities are basically carried out with the aim of obtaining maximum profits to maintain the company's existence amidst competition. Therefore, companies must be more innovative in providing product quality and good service quality to their customers so that they can provide customer satisfaction and the company can be superior to other companies. This research aims to determine the effect of product quality and service quality on customer satisfaction at PT. X. The research method used is a quantitative approach. Data collection methods in this research are interviews, questionnaires (Google Form), and literature study. The population in this research are customers of PT. X. The sampling technique used was quota sampling with a sample size of 30 respondents. The data analysis technique used is multiple linear regression analysis which is processed using the SPSS version 25.0 application. The results of this research indicate that partially product quality has a significant effect on customer satisfaction. Service quality partially has a significant effect on customer satisfaction. Simultaneously, product quality and service quality have a significant effect on customer satisfaction.